Chemical properties of silylchloro derivatives of ethylene and acetylene - V. G. Lakhtin; V. D. Sheludyakov; E. A. Chernyshev (Тонкие химические технологии)
Systematic studies on the chemical properties of a new class of compounds – silylchloro derivatives of ethylene and acetylene – and on regularities of their behavior in hydrosilylation, chlorination, and hydroclorination were reviewed. Quite different behavior of the monomers under study in these reactions was found depending on the amount of chlorine atoms and silyl groups and their positions in the molecule, as well as on the nature of substituents at the silicon atom was found.